Beneficiation of Commiphora africana Plant: Extraction and Application of Green Softener on Cotton Fabric - Fisaha Asmelash; Million Ayele (Journal of Engineering)
This paper aims at the extraction and application of eco- and user-friendly natural gum obtained from Commiphora Africana tree. The result obtained is also compared with fabric treated with a commercial softener of the same concentration. The gum was extracted by puncturing the stem of the plant and the extracted gum was applied directly to 100% cotton fabric through a padding process with different concentrations of extracted gum (i.e., 20 gram per litre (g/l), 25 g/l, and 30 g/l). Another similar fabric sample was treated with a silicon softener of the same concentration. The fabric samples treated with both natural gum and silicon softener were tested for their stiffness, crease recovery, and drapability. The results show that the change in fabric softness depends on the concentration of softener used in both cases. As the concentration of the softener increased, there was a decrease in bending length and drape coefficient for both fabric samples. The drape coefficient of fabric sample treated with natural gum has a comparable result with fabric treated with silicon/commercial softener. Maximum increases in recovery angle were seen in fabric treated with natural gum at a concentration of 30 g/l.